READING CULTURE AMONG THE CHILDREN AND ADOLESCENT IN NIGERIA: A CHALLENGE TO SCHOOL LIBRARIES - CHIWAR, MARY ANTHONY (IJRDO- Journal of Educational Research, 2019)
The paper attempt to discuss the reading culture among the children/adolescents in Nigeria, looking at school libraries as a major source of encouragement to them. The paper highlighted on the role of school libraries in promoting reading culture in primary/secondary schools. It further examines the challenges associated with reading culture in Nigeria. Also, the way forward was carefully proffer to promote reading culture among the children/adolescents. The paper concluded with emphasis that, school library being an important tool for development of reading culture must be given priority by educational planners in Nigeria. Furthermore, school libraries must be provided with relevant and adequate resources that can attract and motivate reading culture for the development of the children/adolescents education and the nation at large.